Elaine Steinbeck in USSR - unknown:::Creator::::::::::::
Mary Jane Bridges (US embassy), with Russian writers Polteralski and Koseshenko, and Elaine Steinbeck taken during the in Oct. 22-26, 1963.Steinbeck's visit .Original in safe